(untitled) (Journal of actual problems of jurisprudence, 2019)
In this paper, the authors examined about topical issues related to tax legislation. These issues require speedy resolution, because can create great difficulties and problems for the normal functioning of the tax system, which hampers economic development and accelerated industrial-innovative development of Kazakhstan